Cartografemas: fragmentos autobiográficos de um artista-professor - SILVA, Jorge Leal Eiró da (2009)
This research is an autobiographical narrative that approaches the life career of the painter and professor Jorge Eiró. The research proposes to investigate the articulation between the activities performed and its implication in its process of formation. Incorporates as a plastic and conceptual reference the visual poetic of its work associated to its esthetic and cultural approximation while production of subjectivity. In this movement, the composition of the narrative writing figures in a cartography and assumes the sense of function, as the concept of Gilles Deleuze and Félix Guatarri, aligning itself in a post-structuralist theoretical perspective. In this conception, subject and object of the autobiographical cartography convert themselves in superject. The narrative elapses in piecemealed reports, scattered but articulated among them, elaborated in a biographem, as the concept of Roland Barthes. The function of the cartography articulated to the form of the biographem constitutes the narrative mix of cartographems. The writing is crossed by cultural references as musical (soundtracks) and literary (literary lira) from the affective memory of the author. The problematization consists in the ways that are articulated and rejected the autobiographical component, enunciated in the biographems. With a bibliographical methodology, this research presents as fundamental categories the autobiography in education, the art and the teaching in art. In the composition of this self-portrait, the theoretical methodological chart of the cartography is featured by cardinal lines of reference from the following authors: Nietzsche, Deleuze and Guatarri that conceptualize the cartography as post-structuralist; Barthes conceives the narrative writing in form of biografemas; Larrosa and Rolnik align the cartographic bearings to an autobiography in education; Argan and Derdyk draw the history and philosophy field of art; finally, Corazza and Silva colour the composition with the philosophy of difference in education and the poetic of an artist-writing.